Discovering the Middle Ages - Cook, William R. (William Robert), 1943-; Herzman, Ronald B.; Stonebarger, Tamara; Dunton, Tom.; Teaching Company (Chantilly, VA : Teaching Co., 2001)
A series of 12 lectures designed to cultivate an understanding and appreciation of the Middle Ages, looking at central themes in medieval culture, art, religion, literature, and history.
disc 1. Medieval and modern -- 2. Monastery and castle -- 3. Cities and towns -- 4. The church and the clergy -- 5. Knights and peasants -- 6. The classical heritage -- disc. 2:7. The Biblical heritage -- 8. The Medieval synthesis -- 9. The presentness of the past -- 10. Surface and depth-Medieval aesthetics -- 11. The language of icons -- 12. Seeing by opposition.
Producer, Tamara Stonebarger ; director, Tom Dunton.
Instructors: William R. Cook and Ronald B. Herzman.
DVD, region 1.
Keywords: Middle Ages; Civilization, Medieval; Europe -- History -- 476-1492.; Educational videos